Doddering but dear … even in the eyes of young children? Age stereotyping and prejudice in childhood and adolescence. (5th May 2017) - Vauclair, Christin‐Melanie; Borges Rodrigues, Ricardo; Marques, Sibila; Esteves, Carla Sofia; Cunha, Filipa; Gerardo, Filomena
Abstract : This study aims to explore age prejudice, and to examine age stereotyping in children and adolescents by adopting the Stereotype Content Model (SCM) as a theoretical framework. It was hypothesised that children are socialised into adopting an ambivalent representation of old age (socialisation hypothesis) and that this cognitive bias becomes weaker in adolescence due to greater cognitive maturity (developmental hypothesis). By analysing representative data from Portugal (European Social Survey; N = 2367), it was ascertained that the ambivalent age stereotype (higher evaluations of warmth than competence for older people) is indeed a shared social representation of older people in Portuguese society. A total of 103 Portuguese children (6–10 year olds) and adolescents (11–15 year olds) were then sampled from a local school and responded to age‐appropriate measures assessing age prejudice as well as age stereotypes. Contrary to previous studies, the findings do not provide evidence for the existence of age prejudice because both children and adolescents reported positive feelings towards older people. However, the socialisation hypothesis was corroborated by showing that the ambivalent old age stereotype was already present in childhood. Contrary to the stipulated developmental hypothesis, the magnitude of this cognitive bias was very similar in adolescence.